MARTINS, Harper Inventory of documents - MARTINS, Harper (ARCA, 2018)
Private papers of H. Martins, First Chaplain of the S.A. Police in Pretoria [1951-1961]
COVERAGE 1914, 1939-1977; 9 Files; 0.11 metre
Keywords: MARTINS, Harper;South African Republican uprisings